Diseño de productos turísticos en base a la fiesta Santísima Cruz en la comunidad de Joseguango Alto. - Centeno Rocha, Liz Karol (2023)
The Holy Cross Festival is a manifestation which is celebrated in the Joseguango Alto community. The products creation helps to commercialize, promote and destinations disseminate, as well as to conserve and take advantage of natural and cultural resources Into compliance with the first aim, it was applied the deductive method with the documentary analysis technique and the methodology for the hierarchy of attractions and generation of tourist spaces into Ecuador 2017, which it was made the PDOT bibliographic review from Mulaló to get the inventory of the tourist attractions from parish. The attractions identification and verification, which were into force, through observation outings. Also, it was identified unregistered attractions and was collected their information, through the file, what proposes the methodology. Subsequently, into aim two, it was used the inductive method with the documentary analysis technique and the methodology for the tourist products planning from Peru, where it was made an analysis about the social, economic and political component from destination. In order to determine the tourist profile, it was applied surveys to the tourists. Based on the got information, it was made the comparison matrix between product and market, then this, it executed the product conceptualization table. The tourist product design was done, through product sheets, food and beverages, lodging and complementary services. The product mapping was made, through the free software Google Earth, having as results 2 tourist products. The third aim has an inductive method approach, it was made with the tourist products FODA matrix tools, already they created, based on the factors, which made up the matrix, it was elaborated the MEFE and MEFI assessment matrices to highlight the products positive aspects, the MAFE matrix had as result offensive, reorientation, defensive, and survival strategies.